METAL–ORGANIC FRAMEWORKS OVERVIEW: STATE OF THE ART - AL-UOBODY, REEM MOHSIN KHALAF; HAMMOODI, HAYDER A.; AMIN, AMIRA (International Journal of Applied Pharmaceutics, 2025)
Metal-organic Frameworks (MOFs) are believed to be a cluster of complexes, metal ions or groups, synchronized with organic ligands. In addition to durable bonds between inorganic and organic groups, reticular synthesis creates MOFs, perfect election of ingredients of which can generate high thermal and chemical stability. Over the few years, the usage of MOFs in biomedical treatments has significantly increased because of their high loading capacities, high surface areas, and precision tunability. A broad range of drug delivery treatments are being investigated for MOFs. MOFs exhibit high drug loading capacities due to their large area and tunable pore sizes. MOFs were first employed to deliver small-molecule medications, then switched to deliver macromolecules, current developments in this area are needed to support this claim. Here, we examine how MOFs have been used historically for drug delivery, paying particular attention to the various ways that MOFs might be designed for certain drug delivery uses. These choices include drug loading, synthesis technique, and MOF structure. Cellular targeting, biocompatibility, tuning, alterations, and uptake are additional factors to consider. This review's overall goal is to direct MOF design toward innovative biological uses.